2011
DOI: 10.2754/avb201180010065
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of CYP19, CYP21 and ER genotypes in Polish Holstein-Friesian cows with regard to the selected reproductive traits

Abstract: The aim of this study was to relate polymorphic variants of CYP19, CYP21 and ER1 genes to reproductive traits in 472 Polish Holstein-Friesian cows. High frequencies of one of the homozygous genotypes were found. The ER1/SnaBI AA homozygotes were not identified. In the first and third lactation, an average calving-to-conception interval (CLVC) in cows of ER1/SnaBI GG genotype was significantly shorter (P ≤ 0.05) than in heterozygous cows. In the cows of ER1/ BglI GG genotype, significantly shorter CLVC (P ≤ 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…1-C). In the opposite to these results in which A allele was not detected, the A allele frequency in the Polish Holstein-Friesian cows was ranged from 92.27 to 93.2% (Szatkowska et al, 2011;Wierzbicki et al, 2014).…”
Section: Pcr-rflp Pattern Of Cyp19 Genementioning
confidence: 80%
See 1 more Smart Citation
“…1-C). In the opposite to these results in which A allele was not detected, the A allele frequency in the Polish Holstein-Friesian cows was ranged from 92.27 to 93.2% (Szatkowska et al, 2011;Wierzbicki et al, 2014).…”
Section: Pcr-rflp Pattern Of Cyp19 Genementioning
confidence: 80%
“…472 Polish Holstein-Friesian cows were screened and found that the calving-toconception interval in the first and third lactation in addition to the calving interval in the third lactation were shorter in AG genotype than AA genotype (Szatkowska et al, 2011).…”
Section: Cyp19mentioning
confidence: 99%
“…In the studies mentioned, it has been proven that the GG homozygotes' lactation lasts longer than the AG heterozygoes' and that the homozygotes need less time to regenerate after a calf's separation, before their next pregnancy and also that their pregnancy lasts slightly longer. (Szatkowska et al 2010). Another study emphasizes importance of the ERs function in the process of developing a mammary gland.…”
Section: The Association Between Milk Yield and The Erα/bgli Genotypementioning
confidence: 99%
“…Sığırlarda yapılan çalışmaların ise sınırlı olduğu ve mevcut çalışmaların genellikle tek bir araştırma grubu tarafından gerçekleştirildiği (Szreder & Zwierzchowski 2004a,b; gözlenmektedir. Bildirilen mutasyonların çeşitli verim özellikleri üzerine etkilerinin incelendiği araştırma sayısı da oldukça sınırlıdır (Szatkowska et al 2011;Zahmatkesh et al 2012). Sığır ERα geninin kodlama yapan ve yapmayan çeşitli bölgelerini kapsayan 2853 bç'lik bir bölgesi ilk kez Szreder & Zwierzchowski (2004a) tarafından ortaya konulmuştur.…”
Section: çIzelge 1-çalışmada Kullanılan Primer Dizileri Ve Restriksiyon Enzimleriunclassified